THE DESIGN AND DEVELOPMENT OF A BANJAR ADAT WEBSITE AS A DIGITAL IMAGE OF SOCIAL LIFE IN BALINESE COMMUNITIES - Bagus Putu Pramana Putra; I Kadek Widiantara; I Putu Gede Budayasa; I Dewa Gede Agung Pandawana (Bulletin of Engineering Science, Technology and Industry, 2026)
The rapid advancement of information technology has driven the need for digital transformation in traditional communities, including Banjar Adat in Bali, which plays a central role in regulating social and cultural life. However, the absence of structured digital media has limited the effectiveness of information dissemination, documentation, and representation of cultural identity. This study aims to design a conceptual model of a website-based information system as a digital representation of the social life of Banjar Adat communities. The research adopts a Research and Development (R&D) approach with a qualitative method in the needs analysis phase. Data were collected through observation, interviews, and documentation involving banjar administrators and community members. The system design process employs a prototype approach, including user needs analysis, system structure design, user interface (UI/UX) design, and feature modeling such as banjar profiles, activity calendars, announcements, and documentation galleries. The results of this study are in the form of a conceptual system design and interface prototype that align with user needs and reflect local cultural values. The findings indicate that the proposed design can serve as a foundational model for developing a website that functions both as an information medium and as a digital image of social life in Balinese communities.